Pendampingan Perangkat Desa Lopana Satu Kabupaten Minahasa Selatan Dalam Upaya Eksplorasi Air Bersih Menggunakan Data Geolistrik : Assistance to Lopana Satu Village Officials, South Minahasa Regency in Exploring Clean Water Efforts Using Geoelectrical Data - Ferdy, Ferdy; Pandara, Dolfie Paulus; Tumbelaka, Agry Yoel; Ponumbol, Yuki Paischa; Maguna, Reynold Alexander (Sam Ratulangi University, 2025)
Lopana One Village, East Amurang District, South Minahasa Regency is a village located in a coastal area with a village area of ​​around 142.30 km2 (BPS South Minahasa Regency) and a fairly dense population with residential or residential homes being very close to each other. coastline. Most of the residents of Lopana Satu village work as fishermen and some also work as farmers, because Lopana village is also the capital of East Amurang sub-district, so many ASN also live in this village. Therefore, the need for clean water is very necessary. The source of clean water in Lopana Satu village only relies on groundwater in the form of dug wells or drilled wells to meet daily living needs. As is known, the cost of making a dug well or drilled well requires quite a large amount of money, so if the coordinates of potential sources of clean water are not known precisely, it can cause financial losses to the community and the village government if they want to make a public well for the Lopana Satu village community. Based on these conditions, it is necessary to carry out assistance activities for clean water exploration using existing geoelectrical data, so that it can provide more accurate information regarding the existence of clean water sources. As a result of this community service activity, the participants felt helped by the existence of this activity. Where in this activity, important information was obtained in the form of the distribution and depth of what is thought to be the groundwater carrying layer with a resistivity value of ≤ 12 ohmmeters and a depth of around 10-40 meters for the first pass and around 15-45 meters for the second pass. Key words: Groundwater exploration, geoelectric data, community assistance, Lopana Satu. ABSTRAK Desa Lopana satu Kecamatan Amurang Timur Kabupaten Minahasa Selatan merupakan salah satu desa yang terletak di daerah pesisir dengan luas desa sekitar 142,30 km2 (BPS Kabupaten Minahasa Selatan) dan jumlah penduduk yang cukup padat dengan jarak pemukiman atau rumah penduduk mempunyai jarak yang sangat dekat dengan garis pantai. Sebagian besar penduduk desa lopana satu berprofesi sebagai nelayan dan sebagian juga ada yang berprofesi sebagai petani, karena desa Lopana juga merupakan ibukota dari kecamatan Amurang Timur sehingga banyak juga ASN yang berdomisili di desa ini. Karena itu kebutuhan akan air bersih sangat di perlukan. Sumber air bersih di desa Lopana satu hanya bergantung pada air tanah berupa sumur gali atau sumur bor untuk memenuhi kebutuhan hidup sehari-hari. Sebagaimana di ketahui biaya membuat sumur gali maupun sumur bor memerlukan biaya yang cukup besar, sehingga jika titik koordinat potensi sumber air bersih tidak di ketahui dengan tepat, dapat membuat kerugian biaya terhadap masyarakat maupun oleh pemerintah desa jika ingin membuat sumur umum untuk masyarakat desa Lopana Satu.Berdasarkan kondisi ini sehingga perlu dilakukan kegiatan pendampingan untuk eksplorasi air bersih menggunakan data geolistrik yang sudah ada, sehingga dapat memberikan informasi yang lebih akurat mengenai keberadaan sumber air bersih.Hasil yang di peroleh dari kegiatan pengabdian kepada Masyarakat ini, para peserta merasa terbantu dengan adanya kegiatan ini. Dimana pada kegiatan ini, diperoleh informasi penting berupa sebaran dan kedalaman yang diduga sebagai lapisan pembawa air tanah dengan nilai resistivitas ≤ 12 ohmmeter serta kedalaman sekitar 10-40 meter untuk lintasan pertama dan sekitar 15-45 meter untuk lintasan kedua.